The Influence of Service Marketing Mix Strategy on the Level of Customer Satisfaction in PT. Bank Bri Pallengu Unit, Barana Village Kec. Bangkala Barat Kab. Jeneponto - Nurlela (Pustaka Digital Indonesia, 2021)
This study aims to determine the extent of the influence of the service marketing mix strategy on the level of customer satisfaction at PT. Bank BRI Pallengu Unit, Barana Village, Kec. West Bangkala Kab. Jeneponto . This type of research used a quantitative approach. Processed data is the result of respondents' interpretation of customers at PT. Bank BRI Pallengu Unit, Barana Village, Kec. West Bangkala Kab. Jeneponto . The analysis technique used in this study uses an interactive model with respondents, where the respondent's interpretation data is then regulated by using data analysis techniques in this case SPSS. Based on the results of data analysis that has been carried out, a simple regression equation model is obtained Y = 1.452 + 0.665 X which means the service marketing mix has a positive effect on customer satisfaction and from the results of the t test analysis obtained a significant value of 0.0 01 < 0.05 which means the service marketing mix has a significant effect on customer satisfaction at PT . Bank BRI Pallengu Unit, Barana Village, Kec. West Bangkala Kab. Jeneponto , thus the hypothesis is accepted.